Measuring and modeling transport properties of actinide and fission product contaminants in unsaturated prairie soil. Issue 2 (1st March 2007) - Sims, David J; Andrews, William S; Wang, Xiaomei; Creber, Katherine A.M
Abstract : This paper presents the results of measuring and modeling the transport of actinides and fission products in unsaturated prairie soil based on the contamination from a storage tank in Alberta. In 1951, a release occurred from an underground storage tank of some 6.7 L of an acidic, aqueous solution containing an estimated 360 GBq (9.7 Ci) of dissolved mixed fission products in a 6.7 L acidic solution. The site where this occurred remained undisturbed for 50 years before soil samples were collected and analyzed for specific radionuclide content, namely Cs-137, U-238, and Sr-90. The measured diffusion coefficients ( D d ) for the selected group of radionuclides were 3.0 × 10 –4 cm 2 s –1 (Cs-137), 1.5 × 10 –5 cm 2 s –1 (U-238), and 2.6 × 10 –3 cm 2 s –1 (Sr-90). Based on transport modeling, after a period of 250 years from the release, the Sr-90 plume would have its maximum concentration at a depth of 2.8 m, while the Cs-137 plume would have its maximum concentration at 0.5 m. It is predicted therefore, that if the three radionuclides should reach the water table depth (50 m) then they will be at a concentration lower than their clearance level values and, hence, will not pose a health hazard. Key words : transport modeling, unsaturated soil, radionuclides, diffusion coefficient, distribution coefficient, uranium, strontium, cesium.